Die rechtliche Lage der deutschen Minderheit im Ungarn der Horthy-Ära - Albrecht, Timo Marcel (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
This publication seeks to provide an overview of the German minority in Hungary during the era of Regent Miklós Horthy (1920–1944), mainly with regard to its legal situation but also beyond. After delivering some background knowledge and facts concerning this minority, its legal status is shown by the examples of the 1920 Treaty of Trianon (forming part of public international law) as well as concerning the laws governing the Hungarian school system (legally on the national level). Moreover, the rising degree of organization within Hungary‘s German minority from the 1920s onwards, exemplified predominantly by the Ungarländisch-Deutscher Volksbildungsverein and the Volksbund der Deutschen in Ungarn, is thematized. Lastly, also the legal effects of the “Volksgruppenabkommen” of Vienna from 1940 as a minority protection agreement between Hungary and the “Third Reich” are addressed. Thereby, this article proves that minority law was a highly political issue and that the legal situation of the Hungarian Germans during the Horthy’s period of office was strongly dependent on the foreign relations between the German Reich and Hungary.